Penguatan Hak Kesehatan Reproduksi Remaja dalam Peraturan Pemerintah No 28 Th 2024 Pada Remaja di Genuksari Kota Semarang - Jamil, Masfufatun; Wahyu Utami, Lucky Restyanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Reproductive health is defined as complete physical, mental and social well-being and not merely the absence of disease or infirmity in all matters relating to the reproductive system. Major Problems of Adolescent Reproductive Health including the lack of information regarding adolescent reproductive health and the problem of shifts in adolescent sexual behavior. In 2023, there were 689 HIV cases in Semarang City, with 77% more cases being suffered by men due to higher male mobility. The government, family and community are responsible for implementing adolescent health efforts. Further provisions are regulated in Government Regulation No. 28 of 2024. For that, strengthening of community independence in detecting reproductive health disorders in adolescents of Karangtaruna Genuksari, Genuk District, Semarang City was carried out. The methods used were pre-test, lecture, discussion and evaluation. The results obtained include: after a pre-test, the majority of respondents' knowledge was sufficient (64%) and after a post-test, knowledge increased to good (84%), partners were consistently able to recognize signs of reproductive health disorders in adolescents and understood government regulations governing health.